2016
DOI: 10.1016/j.anifeedsci.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of adding ruminally protected phenylalanine to rations containing high levels of canola meal on performance of high producing Holstein cows

Abstract: Highlights• Supplementation of Phe to early lactation cows receiving 170 g/kg of diet DM as CM.• Phe changed energy utilization, decreasing milk lactose while increasing BCS gain.• Phe resulted in an increase in whole tract aNDFom and ADF digestibility.• Phe support milk production after restoring mobilized peptides to muscle protein.• Phe regained animal performance lost when CM inclusion was increased. AbstractEven though studies supplementing Phe to dairy cattle are rare, it has been identified as limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…The chemical composition of the ingredients used in the TMR (Table 1) were generally consistent with NRC (2001) values. However, alfalfa hay, Pima cottonseed, wheat and corn silage all had slightly higher CP levels than in previous studies (Swanepoel et al, 2014(Swanepoel et al, , 2015(Swanepoel et al, , 2016a.…”
Section: Diet Evaluationcontrasting
confidence: 67%
See 3 more Smart Citations
“…The chemical composition of the ingredients used in the TMR (Table 1) were generally consistent with NRC (2001) values. However, alfalfa hay, Pima cottonseed, wheat and corn silage all had slightly higher CP levels than in previous studies (Swanepoel et al, 2014(Swanepoel et al, , 2015(Swanepoel et al, , 2016a.…”
Section: Diet Evaluationcontrasting
confidence: 67%
“…At a supplementation level of ~15 g/d of intestinally available Phe (Swanepoel et al, 2015), this NE repartitioning was not at the expense of milk protein and fat synthesis, as was the case with a lower Phe supplementation level of ~7.5 g/d in Swanepoel et al (2016a). The resultant hypothesis;…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, further analyses were performed to investigate the effects of PHE or VAL on protein synthesis-related responses and energy-mediated cellular signaling in MAC-T cells. When high milk-producing Holstein cows fed a rumen protected form of PHE, little or no change in body conditions score were observed and there is either a tendency towards a decrease or no change in true milk protein yield compared to control group [14][15][16]. However, our study showed a significant increase in concentrations of protein in both the cultured medium and within cells after PHE treatment ( Fig.…”
Section: Discussionmentioning
confidence: 49%